Value Added Tax (VAT) Restitution and Revenue - Rizkina, Miftha; Adiman, Sumardi (Lembaga Jurnal & Seminar Universitas Pembangunan Panca Budi, 2023)
The purpose of this study is to determine and analyze the application of VAT refund, VAT revenue and the relationship between VAT refund and VAT revenue. This study was conducted at the Regional Office of DGT I North Sumatra. The research method used in this research is descriptive and the type of data used is qualitative. The data sources used in this study are primary and secondary data using data collection techniques including documentation and interviews. The results of this study indicate that each year not all submissions of restitution or returns can be made due to one of the things such as the submission process for 12 months. And the amount of VAT revenue has increased every year, the increase in value-added tax revenue is also influenced by the value-added tax collection system which currently uses E-Invoicing. The North Sumatra I DGT Regional Office has complied with the Tax Council regulations in implementing VAT restitution.